2005
DOI: 10.1515/epoly.2005.5.1.783
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of polystyrene particles coated by photo-crosslinked block copolymers containing a biocidal polymethacrylate block

Abstract: A commercially available poly(ethylene-co-butylene) copolymer, endcapped by a short polyisoprene block and a hydroxyl group (PI-b-PEB-OH), has been derivatized into a macroinitiator for atom transfer radical polymerization (ATRP) by esterification of the hydroxyl end-group by an activated bromidecontaining acyl bromide. Two types of triblock copolymers, PI-b-PEB-b-poly-(dimethylaminoethyl methacrylate) (PDMAEMA) and PI-b-PEB-b-poly[2-(tert-butylamino)ethyl methacrylate] (PTBAEMA), have been synthesized and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Jérôme and coworkers have published a series of reports on antimicrobial particles, blends, and coatings [82][83][84]. In terms of the synthesis and biological evaluation of their antimicrobial polymers in solution, they have studied a block copolymer, 20, in Fig.…”
Section: Polymers Containing Quaternary Ammoniums or Quaternary Pyridmentioning
confidence: 99%
“…Jérôme and coworkers have published a series of reports on antimicrobial particles, blends, and coatings [82][83][84]. In terms of the synthesis and biological evaluation of their antimicrobial polymers in solution, they have studied a block copolymer, 20, in Fig.…”
Section: Polymers Containing Quaternary Ammoniums or Quaternary Pyridmentioning
confidence: 99%
“…coated with tri-block copolymers of dimethylaminoethyl methacrylate. [13] The polystyrene-silver nanoparticles were modified for antimicrobial activity against Escherichia coli and Staphylococcus aureus. [14,15] The objective of the present work was to evaluate the potential use of chitosan and polystyrene nanoparticles as an additive for antibacterial property on cotton fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…In most previous studies on the antibacterial activity of materials grafted with quaternized pDMAEMA, incubation in the bacterial suspension was for a given short time and the antibacterial effect was measured by simply counting the number of bacteria in the suspension [12][13][14][15]. However, since the bacteria adhere strongly to these materials, simple washing may not detach bacteria.…”
Section: Antibacterial Assaymentioning
confidence: 99%
“…Quaternized pDMAEMA has much higher antibacterial ability than unquaternized pDMAEMA, acting as a cation biocide that has been shown to kill most Gram-negative and Gram-positive bacteria [9]. pDMAEMA has been attached to various flat substrates, including glass [12,13], polystyrene [14] and polypropylene [15]. These materials have been shown to have antibacterial properties, albeit at a modest level, and it has been found that the antibacterial effect increases with the graft density of pDMAEMA [16].…”
Section: Introductionmentioning
confidence: 99%